CREM-transgene mice: An animal model of atrial fibrillation and thrombogenesis. Issue 163 (March 2018) - Bukowska, A.; Felgendreher, M.; Scholz, B.; Wolke, C.; Schulte, J.S.; Fehrmann, E.; Wardelmann, E.; Seidl, M.D.; Lendeckel, U.; Himmler, K.; Gardemann, A.; Goette, A.; et al.
Abstract: Background: The molecular pathomechanisms underlying atrial thrombogenesis are multifactorial and still require detailed investigations. Transgenic mice with cardiomyocyte-directed expression of the transcriptional repressor CREM-IbΔC-X (CREM-TG) represent an experimental model of atrial fibrillation (AF) that shows a gradual, age-dependent progression from atrial ectopy to persistent AF. Importantly, this model develops biatrial thrombi. The molecular characteristics related to the thrombogenesis in CREM-TG mice have not been studied, yet. Methods: The inflammatory and prothrombotic state was evaluated at the transcriptional (qRT-PCR) and protein level in the left (LA) and right atria (RA) from CREM-TG mice at the age of 20 weeks and compared to wild-type controls. Moreover, histological analyses of atrial thrombi were performed. Results: The endocardial dysfunction was mirrored by diminished levels of eNOS-mRNA in both atria (RA: 0.79 ± 0.04, LA: 0.72 ± 0.06; each P < 0.05). Moreover, the PAI-1/t-PA mRNA ratio was significantly increased in both atria (RA: 3.6 ± 0.6; P < 0.01, LA: 4.0 ± 1.0; P < 0.05) indicating a high risk of thrombus formation. However, the inflammatory phenotype was more pronounced in the RA and was reflected by a significant increase in the mRNA levels encoding adhesion molecules ICAM-1 (2.1 ± 0.2; P < 0.01), VCAM-1 (2.3 ± 0.5; P < 0.05), and selectin P (3.6 ± 0.5: P < 0.05). Conclusions: CREM-TG mice represent a valuable model for studying atrial thrombogenesis and assessing therapeutic approaches preventing embolic events in the systemic and pulmonary circulation. Highlights: The CREM-TG mouse model is a valuable one for studying atrial thrombogenesis and therapeutic interventions. This mouse model of atrial fibrillation (AF) showed biatrial thrombi formation. The prothrombotic state in CREM-TG mice largely resembles the prothrombotic profile documented in AF patients. The proinflammatory phenotype is more pronounced in the RA of CREM-TG mice.